Brief Report: Dclk1 Deletion in Tuft Cells Results in Impaired Epithelial Repair After Radiation Injury. (March 2014) - May, Randal; Qu, Dongfeng; Weygant, Nathaniel; Chandrakesan, Parthasarathy; Ali, Naushad; Lightfoot, Stanley A.; Li, Linheng; Sureban, Sripathi M.; Houchen, Courtney W.
Abstract The role of Dclk1+ tuft cells in the replacement of intestinal epithelia and reestablishing the epithelial barrier after severe genotoxic insult is completely unknown. Successful restoration requires precise coordination between the cells within each crypt subunit. While the mechanisms that control this response remain largely uncertain, the radiation model remains an exceptional surrogate for stem cell‐associated crypt loss. Following the creation of Dclk1‐intestinal‐epithelial‐deficient Villin‐Cre;Dclk1flox/flox mice, widespread gene expression changes were detected in isolated intestinal epithelia during homeostasis. While the number of surviving crypts was unaffected, Villin‐Cre;Dclk1flox/flox mice failed to maintain tight junctions and died at approximately 5 days, where Dclk1flox/flox mice lived until day 10 following radiation injury. These findings suggest that Dclk1 plays a functional role critical in the epithelial restorative response. Stem Cells2014;32:822–827